Solar Based Photocatalytic Decolorization of Four Commercial Reactive Dyes Utilizing Bound TiO2-Fe3O4 Nanocomposite - Yoanes Maria Vianney; Ivana Rosalyn; Stephanie Angela (Universitas Gadjah Mada, 2018)
Dye effluent is one of the most prominent source of water contamination. This study investigated the solar based photocatalytic decolorization of four commercial reactive dyes, which are Reactive Turquoise Blue G 133, Reactive Yellow M4g, Reactive Bordeaux B, and Reactive Red M8b using immobilized TiO2-Fe3O4 on three kind of binders as the support, specifically cyanoacrylate glue, oil-based paint, and white Portland cement on PVC plate. TiO2-Fe3O4 was synthesized using sol-gel method and placed in muffle furnace at 773 K. The composite of TiO2-Fe3O4 was characterized using SEM-EDX and XRD. White cement emerged as the best binder in term of the color removal efficiency of all four dyes compared to other binders, which were more than 90% color removal after 3 h of solar irradiation. Moreover, there was significant enhancement on color removal using immobilized photocatalyst on white cement compared to mobile photocatalyst. The kinetic of the decolorization performance followed the pseudo-first-order reaction. The apparent reaction rate constant was found to decrease along with the increase of the dye concentration. The photodecolorization kinetics fitted the Langmuir-Hinshelwood model. These protocols and results can be applied into textile industrial primary wastewater treatment using solar as a sustainable light and energy source.